##### Ads

related to: sec

Triple

**Sec**can be considered a generic and inexpensive version of Cointreau. ... the amount for Cointreau as compared Triple**Sec**, you should.10 Answers · Food & Drink · 24/02/2007

I have lost respect for the

**SEC**due to its extremly weak non-conference scheduling...if you factor beating the cupcakes of the**SEC**(Miss & Miss St.) thats 6...16 Answers · Sports · 31/08/2007

⌠

**sec**^3(x)dx = ⌠**sec**(x)**sec**^2(x)dx u=**sec**x du=**sec**(x)tan(x)dx dv=**sec**^2(x)dx v = tan(x) ⌠**sec**^3(x)dx =**sec**(x...x)- ⌠(**sec**^2(x)-1)**sec**(x)dx ⌠**sec**^3(x)dx =**sec**(x)tan(x)- ⌠(**sec**^2(x)**sec**(x)dx + ⌠**sec**(x)dx transpose ⌠(**sec**^2(x)**sec**(x)dx to...3 Answers · Science & Mathematics · 20/03/2011

Since

**sec**θ = 1/cosθ, consider the sign of cosθ (since**sec**θ and cosθ will have the...cosθ < 0 in Quadrants II and III,**sec**θ < 0 in Quadrants II and III as...1 Answers · Science & Mathematics · 23/08/2011

∫

**sec**^2(x) dx multiply and divide with tan x ∫tan x**sec**^2(x) dx / tan x let tan x = u**sec**^2(x) dx = du now the integral becomes...5 Answers · Science & Mathematics · 03/01/2010

I = ∫

**sec**^n(x) dx = ∫**sec**^(n-2)(x)**sec**^2(x) dx = ∫**sec**^(n-2)(x) dtan(x) =**sec**^(n-2)(x) tan(x) - ∫tan(x) (n-2)**sec**^(n-2) tan(x) dx =**sec**^(n-2)(x) tan(x) - ∫(n-2)**sec**^(n-2) tan^2(x) dx =**sec**^(n-2...3 Answers · Science & Mathematics · 05/02/2011

∫

**sec**(x) tan^4(x) dx For the integrand tan^4(x)**sec**(x), use the trigonometric identity tan^2(x) =**sec**^2(x)-1... the reduction formula, ∫**sec**^m(x) dx = (sin(x)**sec**^(m-1)(x))/(m-1) + (m-2)/(m-1) ∫**sec**^(-2+m)(x) dx, where...2 Answers · Science & Mathematics · 25/10/2010

1.)

**sec**^ 4 -**sec**^ 2 = tan^ 4 + tan^ 2 =**sec**^2x(**sec**^2x-1) =**sec**^2xtan^2x =(1+tan^2x)(tan^2x) =tan^2x+tan^4x answer// 2.) (tan(a...sin^2(a)cos^2(a) ......1..............1 =------------- - ------------- ....cos^2a......sin^2(a) =**sec**^2(a)-csc^2(a) answer//3 Answers · Science & Mathematics · 21/03/2009

**sec**(x) * dx =>**sec**(x) * (**sec**(x) + tan(x)) * dx / (**sec**(x) + tan(x)) => (**sec**(x)^2 * dx +**sec**(x) * tan(x) * dx) / (**sec**(x) + tan(x)) u =**sec**(x) + tan(x) du =**sec**(x) * tan(x) * dx +**sec**(x)^2 * dx du / u ...4 Answers · Science & Mathematics · 17/04/2013

Hello, ∫ tan²θ

**sec**θ dθ = let's start replacing tan²θ with**sec**²θ - 1...dθ - ∫**sec**θ dθ summing up, we have: ∫ tan²θ**sec**θ dθ = ∫**sec**θ**sec**²θ dθ - ∫**sec**θ dθ let's integrate ∫**sec**θ**sec**²θ d...1 Answers · Science & Mathematics · 10/05/2011

##### Ads

related to: sec